121k views
4 votes
Solve the system by elimination.
-6x + y = 0
9x - 8y = 4

Solve the system by elimination. -6x + y = 0 9x - 8y = 4-example-1

1 Answer

2 votes

Answer:

(4, 4 )

Explanation:

Given the 2 equations

- 6x + 6y = 0 → (1)

9x - 8y = 4 → (2)

Multiplying (1) by 3 and (2) by 2 and adding will eliminate the x- term, that is

- 18x + 18y = 0 → (3)

18x - 16y = 8 → (4)

Add (3) and (4) term by term to eliminate x, then

2y = 8 ( divide both sides by 2 )

y = 4

substitute y = 4 into either of the 2 equations and solve for x

Substituting into (2)

9x - 8(4) = 4

9x - 32 = 4 ( add 32 to both sides )

9x = 36 ( divide both sides by 9 )

x = 4

Solution is (4, 4 )

User Walt Corey
by
5.4k points